Neptunium mononitride as a target material for Pu-238 production - Peruski, Kathryn M. (Frontiers in Nuclear Engineering, 2022)
Deep space exploration requires specialized sources for both thermal and power applications. Radioactive decay heat of plutonium-238 (Pu-238) provides these sources in the form of radioisotope thermoelectric generators (RTGs). The Pu-238 is produced via neutron capture reaction involving neptunium-237 (Np-237) target material. Continual optimization of Np-237 target materials and evaluation of potential alternative targets for production of Pu-238 RTGs are advantageous for meeting ongoing space power system resource requirements. Current production of Pu-238 for RTGs for the US space program utilizes neptunium dioxide (NpO2) targets; however, the use of neptunium mononitride (NpN) presents an opportunity to increase the mass of Np-237 per target compared to the dioxide form, as well as increase the thermal conductivity of the target. To assess the viability of a NpN target material, the material chemistry must be thoroughly evaluated, including synthesis methods and dissolution and reprocessing schemes. This review presents a summary of synthesis pathways for NpN based on published literature on actinide mononitrides. Specific literature on NpN is limited, necessitating evaluation of other actinide systems to gather parallels. This suggests a need for additional experimental studies on NpN. A particular limitation in the existing literature is a lack of information on the differences in material characteristics, such as morphology, particle size, and trace chemical impurities, as a function of synthesis method. These parameters may affect subsequent reactor performance or dissolution of irradiated targets. The evaluation of existing literature is presented with a focus on the efficacy of NpN targets for Pu-238 production.